KIPRAH KH.HASYIM ASYâ€™ARI DALAM MENGEMBANGKAN PENDIDIKAN AGAMA ISLAM - A'dlom, Syamsul (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2014)
The purpose of this study (1) to find out KH. Hasyim Ashariâ€™s concept concerning Islamic education (2) to find out KH. Hasyim Ashariâ€™s pace in developing Islamic education. The methods used in this article deduction, induction, comparative and library research methods on the development of Islamic education KH. Hasyim Ashari as a scholar and his role as a public figure. The result of this study that KH. Hasyim Ashari, in the development of Islamic education, can be grouped as follows: at his role as an Islamic educator, he acted and was involved more in the educational institution or boarding school. He played as a pioneer, a founder, a caregiver or a leader, a teacher, an educator, and as well as a driver for its development. As a scholar, he had given many useful fatwas. With the method of â€œIqraâ€ (read) by KH. Hasyim Ashari had led one in the shade of sciences, while with â€œistifadhohâ€ (training) method, he led anyone remember everything he had learned. In addition, he was also well known as Kyai and Ulamaâ€™ who was sincere in giving religious knowledge to his students.Keywords: pace, develop, Islamic education.